Expression of taste molecules in the upper gastrointestinal tract in humans with and without type 2 diabetes. Issue 3 (27th November 2008) - Young, R L; Sutherland, K; Pezos, N; Brierley, S M; Horowitz, M; Rayner, C K; Blackshaw, L A
Abstract : Objective: Nutrient feedback from the small intestine modulates upper gastrointestinal function and energy intake; however, the molecular mechanism of nutrient detection is unknown. In the tongue, sugars are detected via taste T1R2 and T1R3 receptors and signalled via the taste G-protein α-gustducin (Gαgust ) and the transient receptor potential ion channel, TRPM5. These taste molecules are also present in the rodent small intestine, and may regulate gastrointestinal function. Subjects and methods: Absolute transcript levels for T1R2, T1R3, Gαgust and TRPM5 were quantified in gastrointestinal mucosal biopsies from subjects with and without type 2 diabetes; immunohistochemistry was used to locate Gαgust . Effects of luminal glucose on jejunal expression of taste molecules were also quantified in mice. Results: T1R2, T1R3, Gαgust and TRPM5 were preferentially expressed in the proximal small intestine in humans, with immunolabelling for Gαgust localised to solitary cells dispersed throughout the duodenal villous epithelium. Expression of T1R2, T1R3, TRPM5 (all p<0.05) and Gαgust (p<0.001) inversely correlated with blood glucose concentration in type 2 diabetes subjects but, as a group, did not differ from control subjects. Transcript levels of T1R2 were reduced by 84% following jejunal glucose perfusion in mice (p<0.05). Conclusions: Taste molecules are expressed in nutrient detection regions of the proximal small intestine in humans, consistent with a role in "tasting". This taste molecule expression is decreased in diabetic subjects with elevated blood glucose concentration, and decreased by luminal glucose in mice, indicating that intestinal "taste" signalling is under dynamic metabolic and luminal control.